Unraveling Salinity Extreme Events in Coastal Environments: A Winter Focus on the Bay of Brest - Poppeschi, Coline; Charria, Guillaume; Goberville, Eric; Rimmelin-Maury, Peggy; Barrier, Nicolas; Petton, Sébastien; Unterberger, Maximilian; Grossteffan, Emilie; Repecaud, Michel; Quéméner, Loïc; Theetten, Sébastien; Le Roux, Jean-François; et al. (Frontiers in Marine Science, 2021)
Extreme weather events affect coastal marine ecosystems. The increase in intensity and occurrence of such events drive modifications in coastal hydrology and hydrodynamics. Here, focusing on the winter period (from December to March), we investigated long-term (2000-2018) changes in the hydrological properties of the Bay of Brest (French Atlantic coast) as an example of the response of a semi-enclosed bay to extreme weather episodes and large-scale atmospheric circulation patterns. The relationships between extreme weather events and severe low salinity conditions (as a proxy for changes in water density) were investigated using high-frequency in situ observations and high-resolution numerical simulations. The identification of intense episodes was based on the timing, duration and annual occurrence of extreme events. By examining the interannual variability of extreme low salinity events, we detect a patent influence of local and regional weather conditions on atmospheric and oceanic circulation patterns, precipitation and river runoff. We revealed that low salinity events in Brittany were controlled by large-scale forcings: they prevailed during the positive phase of the North Atlantic Oscillation and periods of low occurrences of the Atlantic Ridge weather regime. The increase in severe storms observed in western France since 2010 has led to a doubling of the occurrence and duration of extreme low salinity events in Brittany.